Perlindungan Hukum Terhadap Hak Anak Atas Kecelakaan Lalu Lintas di Kota Tidore - Hakim Hakim (Jurnal Ilmiah Wahana Pendidikan, 2022)
"Legal Protection Against Traffic Accident Victims in the City of Tidore Islands" Traffic problems are a problem that cannot be separated in everyday life, because people are always in contact with traffic. At this time many drivers do not comply with traffic regulations so that it can cause traffic accidents that result in minor injuries or serious injuries. Law Enforcers do not remain silent in dealing with traffic accidents. For this reason, the Government issues traffic regulations through Law no. 22 of 2009 concerning road traffic and transportation. The problems raised in this thesis are the regulation of legal protection for victims of traffic accidents, and the factors that become obstacles in providing legal protection. In this thesis research the author uses a descriptive sociological juridical research method, after processing the data obtained are analyzed qualitatively. Sources of data used are primary data and secondary data. Collecting data by studying literature and conducting interviews. From the research results it is known that the factors; which becomes an obstacle in providing legal protection is caused by the factors of drivers, pedestrians, vehicles, facilities and infrastructure, officers / law enforcement in road traffic. The factor of traffic accidents that often occurs is due to human error (human factor). Furthermore, in article 340 it is mandated that victims of traffic accidents have the right to get help and treatment from the responsible party, and compensation for the losses experienced by victims of traffic accidents because the victim has the right to receive compensation, which in article 229 paragraph (1 ) Law No. 22 of 2009. divides traffic accidents into three groups, namely: a) Minor Traffic Accident, which is an accident that results in damage to Vehicles and/or goods. b)Moderate Traffic Accident, which is an accident that results in minor injuries and damage to Vehicles and/or goods. c) Heavy Traffic Accident, which is an accident that causes the victim to die or be seriously injured.